Reaksi Pembentukan Ester dari Komponen Minyak Atsiri Cengkih (Syzygium aromaticum) Menggunakan Etanol - Islam Adiguna; Robby Purwanto; Desi Kartika Nugroho (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study investigates the esterification reaction of the major constituent of clove essential oil (Syzygiumaromaticum), eugenol, using ethanol as the alcohol reactant. The process was conducted in a closed system with 1 wt% sulfuric acid (H₂SO₄) as a catalyst at temperatures ranging from 50 to 80 °C and a reaction duration of up to 120 minutes. Product characterization was performed using FTIR spectroscopy and GC–MS. The results indicate that the optimum reaction conditions were achieved at 70 °C with an ethanol-to-eugenol molar ratio of 8:1, yielding a maximum conversion of 91%. The FTIR spectrum confirmed ester formation through the appearance of a characteristic carbonyl (C=O) absorption at 1738 cm⁻¹ and a notable decrease in the hydroxyl (O–H) band at 3200–3400 cm⁻¹. Furthermore, GC–MS analysis revealed a dominant chromatographic peak consistent with the molecular structure of ethyl eugenylether, demonstrating the successful completion of the esterification reaction. The kinetic study showed that the reaction followed a pseudo-second-order model with an activation energy of 42.7 kJ/mol, while the mechanistic pathway proceeded via Fischer esterification involving a tetrahedral intermediate. These findings highlight that ester formation from eugenol can be interpreted fundamentally from a molecular and thermodynamic perspective. Moreover, the study reinforces the theoretical concept of esterification in organic chemistry and supports the potential utilization of clove essential oil as a natural feedstock for the synthesis of fragrance compounds and environmentally friendly additives.